Fake currency detection using image processing method - Alimushwan, Munshi Md.; Mohaimin, Akiful; Islam, Rifat; Chowdhury, Shahriar (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.